PELATIHAN PENCATATAN KEUANGAN UNTUK USAHA SAMPINGAN IBU-IBU RUMAH TANGGA DI KELURAHAN CENGKARENG BARAT, KOTA JAKARTA BARAT - I Nyoman Suri Adnyana; Rahmatullah Rahmatullah; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2023)
This community service activity aims to improve the skills of housewives in West Cengkareng Village in recording the finances of their side businesses in a simple and structured manner. Frequently encountered challenges include a lack of understanding of business bookkeeping, mixing personal and business finances, and the lack of routine transaction recording. The activity was conducted through lectures and Q&A sessions, covering recording income and expenses, cash flow management, and preparing simple profit and loss statements. The results of the activity demonstrated an increased understanding among participants regarding the importance of financial record-keeping in supporting the sustainability of side businesses and improving family financial management.